Georg Simmel's Concluding Thoughts Worlds, Lives, Fragments - Beer, David (Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
'This timely book offers a rich critical reflection on Simmel's lesser known later works. It is a hugely enjoyable read: a lively yet serious engagement that reinvigorates those texts, and compels the reader to revisit Simmel's oeuvre with new questions in mind. David Beer offers us a powerful evocation of the detail, depth and range of Simmel's imaginative thinking and how it might inspire us in the present.' -Martin Hand, Queen's University, Canada This book draws upon the work of Georg Simmel to explore the limits, tensions and dynamism of social life through a close analysis of the works produced in the final years of his life and reveals what they might still offer some 100 years later. Focusing on the relationships between worlds, lives and fragments in these works, David Beer opens up a conceptual toolkit for understanding life as both an individual experience and as a deeply social phenomenon. Taking the reader through artistic andmusical forms of inspiration, to the problems of culture and on to the conceptual understanding of lived experience, the book illuminates the richness of Simmel's ideas and thinking. This sophisticated dialogue with Simmel's lesser known later works will provide fresh insights for students and scholars of cultural and social theory and pave the way for a reinvigorated engagement with his ideas. David Beer is Professor of Sociology at the University of York, UK. His previous books include The Data Gaze (2018), Metric Power (2016) and Punk Sociology(2014).